MORPHOMETRIC, MERISTIC, AND GROWTH PATTERNS OF SNAKEHEAD FISH (Channa striata Bloch, 1793) IN SEIPAKURESERVOIR, SUB-DISTRICT KAMPAR KIRI, KAMPAR DISTRICT,RIAU PROVINCE. - Widya Oktavia Nainggolan; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Channa striatais one freshwater fish that inhabit the SeiPaku Reservoir.Information on biological aspects of this fish, including morphometric, meristic, and growth patterns, however, is rare. To understand the morphometrical, meristicalcaracteristics and growth pattern of this fish, a research had been counted from February-April 2019. Fish sampling was carried out in SeiPaku reservoirs six times at intervals of two weeks. There were 97 fishes (256-501 mm SL and 150-1500 gr BW). There were 26 morphological characteristic measured and 11 meristical characteristics counted. The meristicalcaracteristics were as follows D.40-45, P.14-17, V.6, A.22-28, C.12-14. The number of scale in the pre-dorsal fin was 12-18, in the cheek was 8-9, around the body was 38-40, in the caudal peduncle was 14-16, above lateral line was 6-8 and under lateral line was 10-12. There were 3 morphometrical characteristic differences between male and female C. striata.In male fish, distance between the mouth to the base of the pectoral fin, the distance of the pelvic fin to the base of the anal fin, the length of the anal fin is longer than the female fin. The length-weight relationship shown that the growth male and female was allometric positive with a value of b = 3.1651 for females and b = 3.0718 for males. Keywords:Freshwater fish, positive allometric, morphometric characters, meristic characters, growth patterns